2021
DOI: 10.1007/s12063-021-00209-9
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in repurposing an existing manufacturing plant: a total interpretive structural modeling (TISM) approach

Abstract: Repurposing of an existing manufacturing plant is an emerging field due to the increase in emergencies of the covid-19 pandemic with the need of rapid responses which has a wide range of potential applications in sustainment of the manufacturing plant in these unfavourable times and helping of the economy. It makes the manufacturing plant adaptable to changes, makes it productive by manufacturing products that are currently in demand, prevents the dissolution of the plant and thus harvests the maximum potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In the 150 Tg scenario, multiple industrial responses would likely develop in parallel at different paces and with varying degrees of success, as happened during the COVID-19 pandemic 60,61 , potentially including others not considered in this model such as foods from CO 2 (other SCPs 16 , carbohydrates 62 , electrosynthesized foods 17 , etc.) or synthetic fats 19 .…”
Section: Industrial Foodsmentioning
confidence: 99%
“…In the 150 Tg scenario, multiple industrial responses would likely develop in parallel at different paces and with varying degrees of success, as happened during the COVID-19 pandemic 60,61 , potentially including others not considered in this model such as foods from CO 2 (other SCPs 16 , carbohydrates 62 , electrosynthesized foods 17 , etc.) or synthetic fats 19 .…”
Section: Industrial Foodsmentioning
confidence: 99%
“…A more recent repurposing has been the variety of industries repurposing to produce equipment to be used to address the COVID-19 pandemic. Perfume, textiles and electronics factories have been repurposed for producing hand sanitizer, face masks and ventilators respectively (Poduval et al, 2021). This repurposing took place in a matter of weeks, with the most complex products taking 4-12 weeks to get production to a point that it is ready to scale (Betti and Heinzmann, 2020).…”
Section: Preventing Global Faminementioning
confidence: 99%
“…The role of digital transformation in swift repurposing has also been emphasized by Soldatos et al ( 2021 ). Relatedly, Poduval et al ( 2021 ) use a model-based approach to identify and rank 11 types of barriers that played a central role in the repurposing of an existing manufacturing plant. Poduval et al ( 2021 ) show that the identified barriers are interrelated and highlight the complexity of the manufacturing repurposing phenomenon.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Relatedly, Poduval et al ( 2021 ) use a model-based approach to identify and rank 11 types of barriers that played a central role in the repurposing of an existing manufacturing plant. Poduval et al ( 2021 ) show that the identified barriers are interrelated and highlight the complexity of the manufacturing repurposing phenomenon. However, none of these studies have aimed to provide an understanding of all the internal and external factors that affect manufacturing repurposing and their causal relationships.…”
Section: Literature Reviewmentioning
confidence: 99%